2010
DOI: 10.1017/s1930297500001042
|View full text |Cite
|
Sign up to set email alerts
|

Maximizing without difficulty: A modified maximizing scale and its correlates

Abstract: This article presents several studies that replicate and extend previous research on maximizing. A modified scale for measuring individual maximizing tendency is introduced. The scale has adequate psychometric properties and reflects maximizers’ aspirations for high standards and their preference for extensive alternative search, but not the decision difficulty aspect included in several prev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
38
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(44 citation statements)
references
References 28 publications
5
38
0
1
Order By: Relevance
“…In addition to undermining construct validity, including decision difficulty in measures of maximizing is problematic because it is impossible to accurately study the relation between maximizing and decision difficulty when the latter is included in the measurement of the former. Moreover, it builds a negative outcome into measurement, which can then affect what maximizing appears to be related to (e.g., by making maximizing seem more problematic than it may actually be; Cheek & Schwartz, 2016;Dalal et al, 2015;Diab et al, 2008;Hughes & Scholer, 2017;Kim & Miller, 2017;Lai, 2010).…”
Section: Definition/operationalization High Standardsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to undermining construct validity, including decision difficulty in measures of maximizing is problematic because it is impossible to accurately study the relation between maximizing and decision difficulty when the latter is included in the measurement of the former. Moreover, it builds a negative outcome into measurement, which can then affect what maximizing appears to be related to (e.g., by making maximizing seem more problematic than it may actually be; Cheek & Schwartz, 2016;Dalal et al, 2015;Diab et al, 2008;Hughes & Scholer, 2017;Kim & Miller, 2017;Lai, 2010).…”
Section: Definition/operationalization High Standardsmentioning
confidence: 99%
“…Although the inclusion of decision difficulty as part of the first measure of maximizing explains why it originally became a prominent component in many definitions and operationalizations, it is striking that decision difficulty continues to be so frequently considered part of maximizing despite several prominent calls to the contrary (e.g., Cheek & Schwartz, 2016;Dalal et al, 2015;Lai, 2010). Indeed, many recent studies of maximizing have measured decision difficulty as part of maximizing (e.g., French & Meltzer, 2019;Hsieh & Yalch, 2019;Luan & Li, 2017a, 2017b, 2019Smallman & Becker, 2017;Oren, Dar & Liberman, 2018).…”
Section: Definition/operationalization High Standardsmentioning
confidence: 99%
“…Specifically, highachieving students showed low perfectionism in the sports domain but high scores in the academic domain, indicating the domain specificity of perfectionism. Moreover, risk aversion is positively correlated with maximization (Lai, 2010). Risk-averse individuals are more inclined to search for alternatives (Parker et al, 2007), which is one of the main characteristics of maximizers.…”
Section: Within-person Variations Of Maximizationmentioning
confidence: 99%
“…Since the publication of MS (Schwartz et al, 2002), the scale has been shortened (Nenkov et al, 2008) and modified (Lai, 2010;Weinhardt, Morse, Chimeli & Fisher, 2012), and new scales to measure maximization have been developed (Diab et al, 2008;Misuraca, Faraci, Gangemi, Carmeci & Miceli, 2015;Turner et al, 2012). See Cheek and Schwartz (2016) for a list and discussion of the existing maximization scales.…”
Section: Introductionmentioning
confidence: 99%
“…So far, maximization has been studied in the U.S. (e.g., Rim et al, 2011;Schwartz et al, 2002;Turner et al, 2012), Italy (Misuraca et al, 2015), Norway (Lai, 2010), the Netherlands, Belgium, China (Roets, Schwartz & Guan, 2012) and Chile (Moyano-Díaz et al, 2014). Roets et al (2012) found in their cross-cultural study that maximizers in the U.S. and Western Europe report lower well-being than satisficers.…”
Section: Introductionmentioning
confidence: 99%